Inovações tecnológicas e contexto escolar: reflexões necessárias - Cunha, Maira Darido da; Bizelli, Jose Luis [UNESP] (My University, 2015)
In modern society technologies have played an important space exerting influences in different spheres. Today's young people are born immersed in the digital and virtual reality, which has changed the ways of learning, as well as to relate to the world. All this context has intensified the debate on the potential of ICT in education and training means. In this study, we sought to investigate the teachers' vision of ICT in the school environment, how they are being incorporated into the school and the limits and possibilities of the use of ICT in the learning process. Questionnaires were administered to 150 teachers who teach in high school in the state network of São Paulo teaching, but specifically in Piracicaba. Continuing, semi-structured interviews with a group of 8 directors were carried out so that there was a deepening on the issues raised by teachers in the questionnaire. The research brought to light important issues for discussion and referral measures striving to support public policies of integration of ICT in schools. Teachers spoke about the advantages and disadvantages of their use and the process of integration. It was observed that, despite efforts to implementation, there are still problems with infrastructure of schools, teacher training and working conditions

Na sociedade moderna as tecnologias têm ocupado um espaço importante exercendo influências em diferentes esferas. Os jovens já nascem imersos na realidade digital e virtual, o que altera as formas de aprender, bem como, de se relacionar com o mundo. Assim, intensifica-se o debate sobre as potencialidades das TIC em meios educacionais e formativos. Nesse estudo, buscou-se investigar a visão dos professores acerca do uso de inovações tecnológicas no ambiente escolar: os limites e possibilidades para o processo de aprendizagem. A amostra foi delimitada com 150 professores do Ensino Médio da rede estadual de São Paulo, no município de Piracicaba. Em continuidade, foram realizadas entrevistas semi-estruturadas com 8 diretores aprofundando questões levantadas pelos professores no questionário. A pesquisa trouxe à tona aspectos importantes para a discussão e encaminhamento de medidas que busquem auxiliar as políticas públicas de inserção das TIC nas escolas. Os professores elencaram as vantagens e desvantagens do seu uso e seu processo de inserção. Observou-se que, apesar dos esforços para implantação, há problemas com infraestrutura das escolas, formação de professores e condições de trabalho.
Technological innovations and school context: reflections required
Keywords: ICT; Teachers view; Public policy; TIC; Visão dos professores; Políticas públicas